HUBUNGAN ANTARA PENGETAHUAN IBU BERSALIN TERHADAP SIKAP IBU UNTUK MELAKUKAN INISIASI MENYUSU DINI DI DESA MOJOKARANG KECAMATAN DLANGGU MOJOKERTO - Yulianti, Indra; Khalimatus Sa’diya, Lida (JURNAL KEPERAWATAN SEHAT, 2014)
Early initiation of breastfeeding (early latch on) as part of efforts to reduce infant mortality. Several studies have shown that the practice of early initiation of breastfeeding and exclusive breastfeeding up to 6 months is still low in Indonesia. This failure is often caused by the onset of problems include difficulty / grievances and obstacles faced by the mother during early lactation. This type of research is observational analytic approach crossectional. The population in this study all women birthing in Desa Mojokarang District Dlanggu Mojokerto district as many as 35 people. The sampling technique was consecutive sampling as much as 32 respondents. The independent variable was maternal knowledge about early initiation of breastfeeding and the dependent is a maternal attitude to initiate breastfeeding early. Instrument which is used quisioner. Data analysed to use Wilcoxon. The results of this study indicate that most respondents had less knowledge about the early initiation of breastfeeding is 17 people (53%), most respondents being negative is 22 people (69%) and meaningful relationship / significant association between maternal knowledge of the attitude of the mother to initiate breastfeeding early in Village Mojokarang District Dlanggu Mojokerto using Wilcoxon statistical test results obtained p <α = 0.05 is 0.000 <0.05. For that health workers provide information about the initiation of early suckling and provide motivation for mothers to want to implement an early initiation of breastfeeding.Keywords: knowledge, attitudes, early initiation of breastfeeding